Collective scattering of light from disordered atomic clouds - Maximo, Carlos Eduardo (2017)
In this thesis, we investigate the coherent scattering of light by atoms randomly distributed in space. As described by a model of coupled dipoles, the cooperation in the spontaneous emission process results from purely optical interactions between the atomic internal degrees of freedom. In the optically dilute regime, where the atomic medium can be described by a refractive index, we have shown that light can be deflected with the application of a gradient of magnetic field. In the dense regime, short-range interactions appear to suppress Anderson localization of light even in two dimensions, a result which disassembles the common belief that all waves are localized in two dimensions. We also find that the fringe pattern, resulting from the interference between light scattered by an atomic cloud and that of its specular image, is robust to both disorder averaging and saturation. Finally, we demonstrate two-atom bound states in the two-dimensional motion through the long-range optical coupling. This optical binding effect with an atom pair will be important to investigate the all-optical stabilization of large clouds.